Hodgkin lymphoma. (May 2017) - Fields, Paul; Wrench, David
Abstract: Hodgkin lymphoma typically presents as a painless mass and can be subclassified into classical and nodular lymphocyte-predominant forms, each of which has characteristic age of incidence peaks. Most patients who develop Hodgkin lymphoma can now be cured. In view of this, therapy adapted to interim positron emission tomography/computed tomography response has been shown as effective to identify: (1) patients with good-risk disease who may benefit from early attenuation of therapy (to limit risks of long-term treatment-associated complications) while maintaining treatment efficacy; and (2) patients with poor-risk disease who may benefit from early treatment escalation. However, a small proportion of patients are either refractory to or relapse after first-line therapy. For such patients, highly active novel agents may overcome these issues and allow more patients to be cured. In future, such agents might be used as less toxic initial therapy in patients intolerant of current conventional treatment approaches (particularly frail or elderly individuals and those with multiple co-morbidities), while incorporating these agents into upfront combination regimens may limit the chemotherapy resistance that underpins refractory/relapsed disease.